Strategi Event Melalui Akun Instagram @moxy_bandung Pada Masa New Normal - Pardede, Yona Margareth; Rinanto, Ridzki (Jurnal Pustaka Komunikasi, 2023)
Hotel Moxy Bandung has faced the consequence of decreased guest occupancy compared to the pre-pandemic year. The purpose of this research is to investigate and analyze the event strategy through the Instagram account @moxy_bandung during the New Normal period. According to Kotler and Keller (2013), the Marketing Communications Mix functions to enhance the effectiveness and efficiency of marketing communication within the framework of seven communication models. The author focuses on one of these elements, which is the event, and utilizes Instagram @moxy_bandung as a medium to communicate the Virtual Run to Give 2021 event conducted by Hotel Moxy Bandung to boost occupancy and room sales. The research findings reveal that the organization of Virtual Run to Give 2021 possesses favorable characteristics of an event, as described by Shone and Parry (2002), including uniqueness, perishability, intangibility, atmosphere, and personal interaction. The utilization of Instagram also garnered a positive response from the community and followers of @moxy_bandung, as evidenced by interactions on the social media account, including comments, direct messages, and tagging links. Impressions from event participants, who are also followers of the Instagram account @moxy_bandung, were positive and indicated their willingness to participate in similar events when circumstances allow.